Innovation In Service Sector: The Role Of Technology, Network Of Relations, And Knowledge - Anwer, Muhammd Junaid; Iqbal, Muhammad Azher; Khan, Dr. Rao Arif Mahmood; Arshad, Sumera; Sadiq, Allah Nawaz; Alamgir, Muhammad; Ahmad, Zohaib (Migration Letters, 2024)
In the current era, the firms are not competing on the basis of products but today’s competition is on the basis of services. In today’s technological era, the increasing growth of service sector posed a global challenge and at the same time an opportunity for the organizations. This paper gives a clear understanding about the constituents of “resource” for service firms, because with the technological revolution the conceptual definition of a nation’s or firm’s resource has dramatically changed. For this purpose, the knowledge, networks and technology are scrutinized as interdependent elements. The maintenance of network with outside and inside partners and customers of the organization is facilitated only by technology. Technology cuts cost and specifically its radical impact is on the way of thinking about “resources” of a country or firm. This study contends that in service firms, technology, network of relations, and knowledge is the ultimate “resource” that provide potential for innovation. Operationally, novelty can be understanding as an organization’s anticipation to “feel for the consumer” by providing superior value to the customers. Furthermore, it is also arguing in this study that, when a company is capable enough to focus its all energies to think on customer’s behalf, innovation in service then starts.